Ukuran Perusahaan, Profitabilitas, Solvabilitas, dan Opini Audit terhadap Audit Delay - Irena Dewi; Jeffin Utomo; Thomas Firdaus Hutahaean (IPM2KPE, 2022)
This study aims to see how company size, profitability, solvency and audit opinion affect audit delay for infrastructure, utility and transportation companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020. This research method is quantitative descriptive. Purposive sampling was used in this study, and a sample of 16 companies was obtained. Descriptive statistics, classical assumption tests, and multiple and simple linear regression analysis were all used in the data analysis. The results showed, a) firm size (X1) to audit delay has a significant value of 0.001 and a regression coefficient of 85.384; b) profitability (X2) on audit delay has a significant value of 0.249 and a regression coefficient of -1709.575; c) solvency (X3) on audit delay with a significant value of 0.708 and a regression coefficient of 27.319; d) audit opinion (X4) on audit delay with a significant value of 0.858 and a regression coefficient of 239.478; e) company size, profitability, solvency, and audit opinion on audit delay has a significant value of 0.015 and a coefficient of determination of 0.104. In conclusion, firm size (X1) has a significant effect on audit delay, profitability (X2) has no significant effect on audit delay, solvency (X3) has no significant effect on audit delay, audit opinion (X4) has no significant effect on audit delay, and firm size , profitability, solvency, and audit opinion have a significant effect on audit delay Keywords: Audit Delay, Audit Opinion, Profitability, Solvency, Company Size